The Impact of Motivation, Leadership Style, and Communication on Employee Performance: A Study at BPJS Ketenagakerjaan Darmo Surabaya Branch Office - Dela Kristiana; Acep Samsudin (Lavish Opulent Education, 2025)
This study aims to analyze the influence of motivation, leadership style, and communication on employee performance at the BPJS Ketenagakerjaan Darmo Surabaya Branch Office. Motivation, as the main driver of work enthusiasm, affects employee productivity. The applied leadership style plays a role in providing direction, inspiration, and supervision, while effective communication ensures good coordination within the organization. This research employs a quantitative approach using multiple linear regression methods to analyze data collected from employees of the BPJS Ketenagakerjaan Darmo Surabaya Branch Office with sample of 36. The results indicate that motivation, leadership style, and communication have a significant influence on employee performance, both partially and simultaneously. The implications of this study can serve as a reference for management in improving leadership effectiveness, communication systems, and motivational strategies to enhance employee performance.